Sarcopenia and fat tissue distribution in patients with colorectal cancer - V. K. Lyadov; V. N. Yegiyev; A. P. Seryakov; O. V. Kucheruk; Ye. S. Darda; A. Z. Negardinov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study parameters of body composition in operated patients with colorectal cancer. To assess interrelation between received data and treatment results (mortality and postoperative morbidity rate). Material and methods. Original study included data of 113 patients, that were operated in surgical clinic of Federal State-Funded Institution «Medical-andrehabilitational center» of Ministry of Health and Social Development the Russian Federation from February, 2009 to November, 2011. Overall there were 66 women and 47 men, aged 30 to 87 years. The mean body mass index (BMI) was 25±4 kg/m2. Obesity was diagnosed in 12 patients before operation, in 5 body weight deficit was found. Body composition data, including amount of skeletal musculature, subcutaneous fat tissue and visceral fat, estimated at single axial native CT-image at the level of 3rd lumbar vertebra (L3) by specialized software. Sarcopenia was detected as a state at which the volume of sceletal musculature is at the range below 2 standard deviations from the mean level for healthy adults. Differences were considered as statistically significant at p<0,05. Results. Postoperative complications were revealed at 42% of patients, 2,5% of patients died. Sarcopenia was diagnosed in 43% of cases, including for all died patients. Statistically significant correlation between development of morbidity or death and preoperative presence of sarcopenia was found. It was found, that at identical BMI the quantity of sceletal musculature and visceral fat is significantly higher in males, subcutaneous fat tissue, on the contrary, is more developed in females. Conclusions. Sarcopenia is present in 43% of patients with colorectal cancer, its presence correlates with failure of treatment. The further studying of body composition at oncologic patients allows to reveal the group of patients with high probability of postoperative complications.